Impact of Smoking on the Risk of Pancreatitis: A Systematic Review and Meta-Analysis - Ye, Xiaohua; Lu, Guangrong; Huai, Jiaping; Ding, Jin (PLOS ONE, 2015)
Background and objective Cigarette smoking may increase the risk of developing pancreatic cancer, although its impact on pancreatitis has only been discerned in recent years. However, the results of previous studies differ. We performed a meta-analysis to provide a quantitative pooled risk estimate of the association of cigarette smoking with pancreatitis. Method A literature search of the MEDLINE and Embase databases was conducted, and studies were selected that investigated the association of cigarette smoking with pancreatitis. Summary relative risks (RRs) with 95% confidence intervals (CIs) were pooled using a random-effects model. Results Twenty-two studies were included. The summary RRs (95% CI) associated with ever, current and former smokers for acute and chronic pancreatitis (AP/CP) were as follows: 1.51 (1.10, 2.07)/3.00 (1.46, 6.17), 1.42 (1.08, 1.87)/2.72 (1.74, 4.24), and 1.22 (0.99, 1.52)/1.27 (1.00, 1.62), respectively. Moreover, studies that analyzed both AP and CP were also summarized: 1.73 (1.18, 2.54) for ever smokers, 1.67 (1.03, 2.68) for current smokers and 1.56 (1.16, 2.11) for former smokers, respectively. There was no evidence of publication bias across the studies. Conclusion The evidence suggests a positive association of cigarette smoking with the development of pancreatitis. It is possible that smoking cessation may be a useful strategy for the management of pancreatitis.